ANALISIS KINERJA KEUANGAN PDAM KOTA SURAKARTA BERDASARKAN KEP.MENDAGRI NO. 47 TAHUN 1999 - Titisari, Kartika Hendra (PARADIGMA, 2010)
The objective of this research was to determine and describe the development of the financial performance of the PDAM in Surakarta on the years 2006-2008 based on the Surat Keputusan Menteri Dalam Negeri Nomor 47 Tahun 1999. Methods used in this research is descriptive method of documentary analysis model. Population is the financial statements (report income statement and balance sheet) of PDAM Surakarta on the years 2006-2008. Data collection techniques used are documentation techniques. Data analysis technique used is based on the Surat Keputusan Menteri Dalam Negeri Nomor 47 Tahun 1999 on guidelines for performance appraisal of the PDAM (Local Water Company). Based on research results can be concluded that: (1) The financial performance of the year 2006-2008 was low. (2) As a whole of 10 (ten) there are three indicators are good indicators of performance are: the ratio of productive assets to the water sales, billing period, and the effectiveness of billing. (3), While financial performance indicators are not maximized value: the ratio of long-term debt to equity, the ratio of operating expenses to income, and operating profit ratio of depreciation. With the condition, PDAM of Surakarta taps should be able to improve efficiency, so that comparison between companies with a cost advantage which is getting better. Besides, it is necessary to check for water leaks that occur in order to reduce losses experienced by the company. Key word    : financial performance, financial ratio, SK Menteri Dalam Negeri Nomor 47 Tahun 1999